ANALISIS EFEKTIVITAS KINERJA KARYAWAN DALAM MENINGKATKAN PRODUKTIVITAS PADA PT. MAYORA INDAH TBK DIVISI MALKIS KOPYOR - Melan Melan; Ari Apriani (Taksasila Edukasi Insani, 2026)
This study aims to examine the influencer of work motivation, work discipline, and work environment on employee and its impact on work environment on employee performance and its impact on work productivity at PT. Mayora Indah Tbk. Malkis Kopyor Division. Using a quantitative descriptive verificative approach, this research employed a slovin-based sampling technique with 124 respodents from the production unit. Data were collected using a structured questionnaire and analyzed throught descriptive statistics and causal hypothesis testing. The findings reveal that work motivation, work discipline, and causal work environment each contribute positively to employee performance. Furthermore, employee performance functions as a mediating variable that strengthens the indirect effect of the three independent variables on work productivity. These result highlight the importance of internal employee factors and workplace conditions as strategic determinants of productivity improvenment within the food manufacturing industry. The study offers empirical evidence that enhancing motivation, ensuring consisent discipline, and maintaining a supportive work environment can significantly improve both performance and productivity outcomes. The novelty of this research lies in integrating employee performance as an intervening variable within the context of production intensive industrial setting.Keywords : employee performance, job discipline, job motivation, work environment, work productivity.